Density of the painted comber Serranus scriba, a goby predator, at an ambient (380 μatm) and high (850 μatm) CO2 sites off a volcanic CO2 vent in Vulcano island, Italy - Davide Spatafora; Carlo Cattano; Giorgio Aglieri; Federico Quattrocchi; Gabriele Turco; Piero Calosi; Marco Milazzo (PANGAEA, 2023)
This data set contains the density of the painted comber predator Serranus scriba at two CO2 sites (Ambient and High CO2). The density of the predator was visually assessed in replicate 10 exttimes 2 m belt transects at 1–3 m depth on mixed sandy/rocky bottoms in the two CO2 condition sites (ambient, n = 19; high-CO2, n = 22).